Preliminary study on deformation behaviors of spray droplet impacting on nonrigid deposited layer. Issue 5 (2nd August 2021) - Cao, Fuyang; Yu, Lei; Zhang, Lunyong; Shen, Hongxian; Jiang, Sida; Gu, Xu; Song, Heqian; Ning, Zhiliang; Huang, Yongjiang; Sun, Jianfei
Abstract: Spray forming technology has been adopted to prepare essential castings in various industry fields. Understanding what happen during the impaction of droplet on deposited layer is critical to optimize spray forming processes and so improve the final casting quality. The present work investigated the morphology evolution of droplet and deposited layer during impaction, with particularly emphasis on the nonrigid feature of deposited layer in practical spray forming. The results demonstrate that the deposited layer would suffer obvious deformation under the impaction of flighting droplet, which produce puddle‐like structure on the deposited layer. The droplet spreading process would be suppressed by this puddle‐like structure when the droplet temperature is not high enough, which might introduce gap between the droplet and the deposited layer, so might cause tiny holes in the final casting. Moreover, the simulation results suggest that multiple droplet impaction might cause column structure on the deposited layer, this would seriously increase the surface roughness of the final casting. The investigations hint that the mechanical properties of deposited layer should be considered when studying the microstructure evolution and mechanism of spray forming casting.